PERADILAN SEBAGAI PILAR NEGARA HUKUM DALAM PERSPEKTIF PANCASILA - Sunarjo Sunarjo (Jurnal Cakrawala Hukum, 2017)
Indonesia was constitutional state based on Pancasila. Thus, it was called Pancasila constitutional state.It wasdifferent from Rechtsstaat or the rule of law. All regulations in Indonesia might not contradict Pancasila as thesource of all constitution. Pancasila constitutional state had a special characteristic namely the harmonyrelation between government and people based on harmony principle: functional relation which was proportionalamong the powers; the balance between right and obligation; the guarantee to the freedom of religion inpositive connotation; good relation between religion and state; and the solution principle of disagreementthrough discussion and judicature as the last medium. Based on the last characteristic, it could be known thatthe solution for every quarrel or disagreement that happened was discussion to reach an agreement. If it did notwork, then the judicature as the last way was taken fairly based on value of Pancasila. Besides, judicature alsohad to be done as the principles of good judicature.